A new approach for measuring corporate reputation - Feldman,Percy Marquina (2014)
This study describes the concept of corporate reputation and reviews some of the major points that exist when it comes to measuring it. It thus suggests a new index for measurement and its advantages and disadvantages are pointed out. The consistency of the seven key variables for the collecting indicator is described by the results of a factor analysis and correlations. Finally, the indicator is put to test by gathering the perception of corporate reputation of 1500 individuals for 69 companies belonging to 15 different industrial sectors, in Peru. The results indicate that the proposed index variables are not necessarily of greatest interest to the study sample in which companies have a better performance. Also greater memorial companies aren't necessarily those that enjoy a greater corporate reputation. Managerial implications for the organizations in the process of managing and monitoring the dimensions involved of this key asset are also referenced.